2023
DOI: 10.3389/fpubh.2023.1055440
|View full text |Cite
|
Sign up to set email alerts
|

Association between use of psychotropic medications prior to SARS-COV-2 infection and trajectories of COVID-19 recovery: Findings from the prospective Predi-COVID cohort study

Abstract: Psychological disturbances are frequent following COVID-19. However, there is not much information about whether pre-existing psychological disorders are associated with the severity and evolution of COVID-19. We aimed to explore the associations between regular psychotropic medication use (PM) before infection as a proxy for mood or anxiety disorders with COVID-19 recovery trajectories. We used data from the Predi-COVID study. We followed adults, tested positive for SARS-CoV-2 and collected demographics, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…These results suggested that psychological distress at the post-acute phase wasassociated with prolonged PASC of any type. Inaddition to the mental health problems observed before the post-acute phase [15,[18][19][20]22,23,66], psychological distress after PASC becomes apparent may lead to prolonged Psychological distress was not associated with prolong neurological symptoms, supporting previous findings that the oresence of psychological distress did not differ significantly between those with edaltering smell or taste after COVID-19 infection and those without [13].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These results suggested that psychological distress at the post-acute phase wasassociated with prolonged PASC of any type. Inaddition to the mental health problems observed before the post-acute phase [15,[18][19][20]22,23,66], psychological distress after PASC becomes apparent may lead to prolonged Psychological distress was not associated with prolong neurological symptoms, supporting previous findings that the oresence of psychological distress did not differ significantly between those with edaltering smell or taste after COVID-19 infection and those without [13].…”
Section: Discussionsupporting
confidence: 67%
“…The association between preexisting mental health problems and PASC has been reported in several cross-sectional surveys [13][14][15][16][17]. According to several longitudinal studies, preexisting mental health problems predict PASC at 3, 12, and 15 months after infection [15,[18][19][20]]. An extensive cohort study reported that pre-existing depression predicted prolonged PASC after 6, 12, and 18 months passed [21].…”
Section: Introductionmentioning
confidence: 99%